Apoptosis and Medicine - Ntuli, Tobias M. (IntechOpen, 2012)
This book looks at the latest research studies on apoptosis in medicine. It is divided into three sections for convenient and easy reading. The first section which comprises two chapters is an introduction of the subject of apoptosis to the uninitiated. The second section which comprises a single solitary chapter looks at apoptosis in normal physiology during bone resorption under mechanical stress. The third and the final section reviews apoptosis in a number of pathological conditions with an emphasis on cancer.